IDENTIFIKASI POTENSI SERTA MINAT KONSUMEN AKAN EKOWISATA MANGROVE DI PULAU BENGKALIS - Dwi Astuti; Teguh Widodo (Inovbiz: Jurnal Inovasi Bisnis, 2018)
Although the government has made various efforts to encourage the sustainable use of coastal and marine resources, utilization patterns that are damaging and threaten the sustainability of coastal and marine resources are still ongoing. This is due to the pressing of need for life, which is getting higher and higher. Development of mangrove ecotourism is one of the alternative development that can help overcome the problem. Utilization of mangrove ecosystem for the concept of tourism (ecotourism) in line with the change in the interest of tourists from old tourism as a new tourism. The purpose of this research is to identify the potential of ecotourism and to determine ecotourism development strategy in Bengkalis Island. The research method used for data type is quantitative and qualitative data with data source in the form of primary data and secondary data. Data collection conducted through questioner, survey method, literature and documentation. Furthermore, the data analysis used is using quantitative and qualitative data analysis methods. The results of the research show that the potential of mangrove ecotourism in Bengkalis Island that can be identified is located in Bengkalis, Bantan, Rupat, Bukit Batu, Siak Kecil and Bandar Laksamana subdistricts. Based on the processing of questionnaire data, the results obtained if consumer interest in mangrove ecotourism on Bengkalis Island, is dominated by referential interest, where the respondents want that mangrove ecotourism on Bengkalis Island is better known and in demand.